(untitled) (Semiárida, 2024)
The objective of this work was to evaluate, in a loamy soil of the caldén forest with lower and higher vegetation cover (Open and Closed respectively), the effect of temperature on total organic carbon contents (TOC) and particle size distribution (PSD), which define micro-aggregation. Composite samples were taken from both sites and calcined for five minutes at 100, 200, 300, 400, 500 and 600 ºC for 5 minutes. On calcined and un-calcined samples, TOC and PSD under high and low dispersion treatment were analyzed. The erodible fraction (EF, particles ≤0.84 mm), which defines the susceptibility of the soil to wind erosion and, a microaggregation index (MiA) were calculated. At both sites, temperature increases reduce TOC from 400 °C onwards. PSD showed reductions in clay fraction and increases in coarse silt from 400-500 °C. Sand fractions <250 μm increased at 500-600 ºC, while those >250 μm decreased. Increases in sand content and reductions in clay content, with increasing temperatures, increased EF at both sites, indicating greater susceptibility of the soil to wind erosion. At 600 °C, in both sites, changes in granulometry produced changes in soil texture. Reductions in TOC, clay and fine silt fractions decreased MiA with increasing temperature. This indicate that agents favoring aggregate formation and stability are lost or transformed at high temperatures. Microaggregates of 125-1000 µm decreased and those of 30-250 µm increased. These aggregates would be formed by the recrystallization of Fe and Al compounds (dense microaggregates), due to the combustion of TOC and reduction of the finest and most reactive soil fraction.